Biomass pretreatment by metal oxides for reducing sugar degradation and water consumption in biofuel production - Li, Jun (Kansas State University, 2020)
Pretreatment is the first step of the three major steps (pretreatment, saccharification, and fermentation) for cellulosic ethanol production. The performance of pretreatment largely determines the performances of downstream saccharification and fermentation as well as whole economic feasibility for cellulosic ethanol production. Although dilute acid pretreatment has been industrialized and liquid hot water (LHW) pretreatment is considered as a green process due to no chemical use in the pretreatment step, both of them cause sugar degradation and inhibitor formation. The formation of inhibitors not only causes sugar loss but also inhibits downstream enzyme and yeast activities, especially during high-solids saccharification and fermentation, consequently lowering the final ethanol yield. The goal of this research was to develop a new pretreatment method to reduce sugar degradation, increase sugar recovery, reduce water usage for inhibitor removal, and eliminate the use of acid-resistant equipment. Five metal oxides, Fe₂O₃, CuO, NiO, ZnO, and MgO, were investigated as catalysts to reduce sugar degradation and improve sugar recovery during corn stover pretreatment. LHW pretreatment was used as control. Among the ﬁve metal oxides, MgO was the most suitable catalyst for biomass pretreatment. The optimal pretreatment condition was 10% solids loading with 0.08 mol/L MgO at 190 °C for 40 min. Compared to LHW pretreatment, MgO pretreatment caused twice hemicellulose recovery and reduced pseudo-lignin formation with pretreatment slurry of neutral pH and trace amounts of furfural and 5-hydroxymethlfufural. Under the optimal pretreatment (as above) and saccharification (10% solids loading, 30/18 µL CTec3/NS22244/g treated biomass, 52 °C, and 72 h) conditions, the double hemicellulose recovery increased xylose yield by 20% and total sugar yield by 6% without sacrificing glucose yield. Biomass slurry from MgO pretreatment was nearly neutral and free of furfural and 5-hydroxymethylfurfural, which allowed the direct integration of MgO-treated biomass and biomass liquor for enzymatic saccharification. Under the same saccharification condition (40/24 µL CTec3/NS22244/g treated biomass, 52 °C, and 72 h), MgO-treated corn stover with pretreatment liquor had a lower glucose yield (71 vs. 75%) but xylose yield was much higher than that from MgO-treated corn stover only (66 vs. 36%), resulting in no significant difference in total sugar concentration (57 vs. 58 g/L). Corn stover slurry with near-neutral pH and free of 5-hydroxymethylfurfural and furfural eliminated the need for washing and detoxification after pretreatment, lightening the burden for wastewater treatment. Combination of MgO and ethanol was used to further enhance sugar recovery, reduce sugar degradation, and enhance enzymatic saccharification. The optimal pretreatment condition was 50% ethanol, 0.07 mol/L MgO, and 10% solid loading at 190 °C for 40 min. Under optimal condition, glucan was completely recovered along with 89.3% xylan recovery and 44.1% lignin removal. Corn stover pretreated by MgO and 50% ethanol achieved 75% glucan and 71% xylan conversions at the 10% solids loading and 30/18 µL CTec3/NS22244/g treated biomass. Under the same saccharification condition, corn stover pretreated by MgO and 30% ethanol had higher glucan and xylan conversions (80 and 78%). This result indicates that excessive xylan recovery from MgO and 50% ethanol pretreatment reduced enzymatic accessibility to cellulose and hemicellulose. When solids loading reached 16%, 74% glucan and 75% xylan conversions were obtained with glucose and xylose concentrations of 71 and 29 g/L. The total sugar concentration exceeded the 80 g/L minimum sugar concentration requirement for economic ethanol distillation. A 16%-solids loading largely reduced the poor mixing issue.
Keywords: Corn stover; MgO pretreatment; MgO-ethanol pretreatment; Sugar recovery and degradation; Lignin removal; Enzymatic hydrolysis